Implementation of Local Wisdom Communication "Malaqbiq" As Character Education in the Teaching and Learning Process In Fisip Unsulbar - Muhammad Sulthan (Indonesia Prime, 2020)
Local wisdom "malaqbiq" is very necessary to always be communicated to our students in educational institutions ranging from kindergarten to higher education, both formil and non-formil so that students still know their identity even though the changing times are always changing because local wisdom is the cultural roots of an area in the harmony of life. The research method used is descriptive qualitative which is presented in Fisip Unsulbar students of the class of 2018 political science study program. The results showed that in general, students of Fisip Unsulbar class of 2018 political science study program still uphold the value of local wisdom "malaqbiq" malaqbiq pau, malaqbiq gauq (good behavior) and malaqbiq kedzo (good behavior).